Use of alcohol among adolescent students: a pilot test - Dallo, Luana; Martins, Raul Aragão (Paidéia (Ribeirão Preto), 2011)
The consumption of alcohol among adolescents is an issue that concerns health professionals given the harm it causes and the indifference of the society regarding its use in this age range. This study analyzed the use of alcohol among high school students in three schools in Cascavel, PR, Brazil. The Alcohol Use Disorders Identification Test (AUDIT) was used and data concerning socioeconomic information, religion, and whether there was abusive consumption of alcohol in the family were also collected. The results revealed that 34.7% of the students present abusive consumption. No statistically significant differences were found concerning schools, gender, and socioeconomic conditions. Having a family member who consumes alcohol was considered a risk factor and having a religion was considered a protection factor. This study shows the need of further studies to warn the society in Paraná aiming the development of public policies including prevention and intervention projects directed to adolescents.